ANALISIS KONSUMSI DAYA DAN LAJU ALIRAN MASSA PADA PROSES DAUR ULANG LIMBAH SAMPAH PLASTIK MENGGUNAKAN MESIN INJECTION MOLDING - Kismanti, Shinta Tri; Firdan, Muhammad; Backhris, Muhammad; Lissa, Hermei (POLITALA PRESS, 2023)
The injection molding machine in this research is a vertical injection machine that is capable of processing chopped plastic bottles for drinking water into more useful products. The temperature required for HDPE plastic waste is 300℃ and requires 1035 Watts of power, while PP plastic waste uses a temperature of 164℃ with a power of 957 watts. The melt flow rate for HDPE type waste is 0.58 ?⁄? while for PP type waste it is 0.59?⁄? so there is a difference of 0.1 ?⁄?.